Research on the Influence of Knowledge Capital on the Performance of New Ventures - Shurui, Qi (Business Administration and Economics Review, 2025)
When the market is extremely competitive during periods where the economy is in transition, new ventures can use the knowledge capital to improve their performance. The role of knowledge capital in helping to develop social networks, providing access to key resources, obtaining market intelligence and entrepreneurship innovation. However, the exact mechanisms by which knowledge capital impacts the survival and growth of new ventures remain poorly understood. This study employs a mixed methods approach, combining a thorough literature review, surveys, and interviews to explore how knowledge capital relates to the performance of new ventures. This research draws on empirical data from 509 new ventures to examine the impact of knowledge capital on the survival, growth trajectories, and performance of new ventures. This study offers actionable insights for entrepreneurs, investors, and policymakers by promoting sustainable development and formulating strategy for the management of new ventures in increasingly competitive markets